A mild and efficient oxidative degradation system of epoxy thermosets: full recovery and degradation mechanism. Issue 18 (31st August 2022) - Long, Yuwei; Tian, Fei; Bai, Lan; An, Wenli; Zhao, Xu; Du, Rongcheng; Liu, Xuehui; Zhou, Xuelian; Xu, Shimei; Wang, Yu-Zhong
Abstract : An efficient oxidation degradation is achieved together with full recovery of the degradation product via the selective cleavage of the C–C and C–O bonds in the hydroxyethyl ether unit, and the C–N bonds using the ammonium ceric nitrate system. Abstract : Despite its high energy efficiency, the oxidative degradation of thermosetting resins has some limitations in practical application due to the complexity and non-selectivity of the oxidation reaction. Here, ammonium ceric nitrate (CAN) aqueous solution was used as the oxidative system to achieve complete and controllable degradation of amine cured epoxy resin (EP) and a 99% degradation rate could be achieved in 1 h at 60 °C. Exploration of the mechanism revealed that the hydroxyethyl ether unit had an important role in the degradation, and degradation products with a high molecular weight ( M w > 8000) were obtained. The resin and CAN can be recycled and reutilised as adhesives, and a high-efficiency catalyst, respectively. In particular, commercial carbon fibre reinforced epoxy resin composite (CFRP) can also be recycled by this degradation system, with the acquisition of nearly non-destructive fibres and resin degradation products that can also be used for bonding.